2018
DOI: 10.1016/j.ecolmodel.2018.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Parameter uncertainty and sensitivity analysis of water quality model in Lake Taihu, China

Abstract: This is a repository copy of Parameter uncertainty and sensitivity analysis of water quality model in Lake Taihu, China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(34 citation statements)
references
References 69 publications
1
33
0
Order By: Relevance
“…However, the mean percent error (13.4%) and mean absolute percent error (58.2%) indicated that further improvements, for example, by reducing the uncertainty of the model inputs and/or by improving the parameter calibration, should be made. Jiang et al [57] simulated the Chl- a concentrations in different subareas of Lake Taihu using a 40-parameter environmental fluid dynamics code (EFDC) model and found that the fitted Chl- a concentrations were basically consistent with field observations. The analyses of the sensitivity and uncertainty of the simulations imply that the observed Chl- a concentrations, water temperature, light, and simulation time are primary factors influencing the EFDC simulation accuracy.…”
Section: Discussionmentioning
confidence: 92%
“…However, the mean percent error (13.4%) and mean absolute percent error (58.2%) indicated that further improvements, for example, by reducing the uncertainty of the model inputs and/or by improving the parameter calibration, should be made. Jiang et al [57] simulated the Chl- a concentrations in different subareas of Lake Taihu using a 40-parameter environmental fluid dynamics code (EFDC) model and found that the fitted Chl- a concentrations were basically consistent with field observations. The analyses of the sensitivity and uncertainty of the simulations imply that the observed Chl- a concentrations, water temperature, light, and simulation time are primary factors influencing the EFDC simulation accuracy.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, a possible reason for the insensitive responses to climatic‐driven hydrologic variability is that the temperature rate coefficient for algal growth is only related to water temperature with a functional curve in the model (Cole & Wells, ). However, water temperature gradients changed with climatic‐driven hydrologic conditions and inflow temperatures, and this coefficient might be improved if it varies according to the seasonal temperatures and is flow dependent on multivariable gradient curves (Jiang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…At a low pH value, dissolved oxygen content will decrease, which can directly affect the life of aquatic biota. At high pH values, the solubility of metal compounds decreases, followed by the development of decomposition rate, which has an impact on the decline of dissolved oxygen value [21].…”
Section: Sediment Sampling and In Situ Water Analysismentioning
confidence: 99%